Vehicles - Ganeri, Anita; Bower, Jeremy (Leicestershire, United Kingdom : Ladybird, 1994)
One of a series, this book covers a wide range of different types of land, air and sea transport and explains how cars, trains, boats, planes and other vehicles work.
Includes glossary
Primary
Keywords: Vehicles; Transportation -- Juvenile literature